(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Research on the Novels of Anita Desai makes it her mission to investigate the man-womanconnection as it is portrayed in the books. She also examines the strategies that the characters have usedto find solutions to the challenges that they face in their life. A study of the author is both intriguing andgratifying to the student who undertakes it. Anita Desai is widely regarded as the preeminent creative forceworking in the field of English literature. Anita Desai is the subject of many critical articles, includingseveral full-length studies, which have been published independently. In this research, an effort is madeto analyze the numerous female characteristics against the backdrop of significant parts of a woman’slife, such as maternity, migration, marriage, and midlife. In most Desai’s works, it is shown that thecouple’s marriage is one of incompatibility. Because she writes about the quandary that contemporaryman finds himself in, her literature is timeless and applicable to all eras. She probes the depths of themind and sees beyond the surface of the skin and the body. Literature is not a way of escape from realityfor her rather, it is an activity of discovery and investigation. Desai focuses the most of her writing onthe horrible circumstances in which women are forced to live by their callous and inconsiderate dadsand brothers. Because of their uniqueness, most of her characters are estranged from the outside world,from society, from their families and parents, and even from themselves. Because of this, characters inman-woman relationships experience feelings of estrangement, withdrawal, loneliness, isolation, and abreakdown in communication. As a result, the purpose of this article is to investigate how these modernIndian women authors in English depict female characters in their works.